A way of being: Women of color educators and their ongoing commitments to critical consciousness. (June 2019) - Kohli, Rita; Lin, Yu-Chi; Ha, Nhung; Jose, Amarilyz; Shini, Chadi
Abstract: Interviews with U.S.-based, justice-oriented, women of Color educators reveal critical consciousness embedded in their positionality, across all domains of their life, not something cultivated just in their teacher development. Through their families and communities, critical educational experiences from K-16+, and continued access to critical discourse, critical consciousness was a way of both understanding and being in the world. Recognizing the complex and continuous labor that goes into developing as a justice-oriented teacher, we argue that teacher education programs and schools must recruit and support those already engaged in developing their critical consciousness. Highlights: Familial and community were foundational to critical consciousness development in justice-oriented teachers of Color. Most participants articulated that teacher education was not a key contributor to their critical consciousness. Teachers of Color were sustained by on-going participation in Critical Professional Development (CPD). Authors argue for the recruitement of teachers oriented towards culturally sustaining teaching practices.